Influence of Patient and Hospital Characteristics on the Performance of Direct Reconstruction after Mastectomy - Hartrampf, J.; Ansmann, L.; Wesselmann, S.; Beckmann, Matthias; Pfaff, H.; Kowalski, C. (Geburtshilfe und Frauenheilkunde, 2014)
Aim: International studies have shown that the performance of a direct (or immediate) reconstruction (DR) after mastectomy is associated with patient (e.g., socio-economic status, insurance status, age) and hospital (number of cases, teaching status) characteristics. The present article addresses the question if such relationships also exist in Germany. Material and Methods: The results of a nationwide questionnaire to the patients of certified breast cancer centres were coupled with the clinical features of the patients and the characteristics of the hospital. Predictors for receiving a DR (vs. delayed or no reconstruction) were estimated by means of a logistic multilevel model for a sample of 1165 patients from 105 certified locations. Results: Substantial differences between the treating hospitals were found (intraclass correlation coefficient null model: 0.195) which can in part be explained by the total model (total model: 0.169). Patients with the following features are more likely to receive a DR: younger age, private health insurance, secondary school leaving certificate (vs. primary school leaving certificate), lower stage and acquisition of more information about reconstruction. ASA and partnership status are not statistically significantly related with DR. DR is more likely to be performed in hospitals with higher caseload of patients with primary breast cancer. Teaching status, operations per surgeon and urbanity of the location are not related to receiving a DR. Conclusions: Non-clinical features of the patients and the primary case number are associated with the performance of a DR, this poses questions concerning reasons and the equality of health care.
EVALuna2:17452